2011
DOI: 10.1038/ncomms1307
|View full text |Cite
|
Sign up to set email alerts
|

Mutual adaptation of a membrane protein and its lipid bilayer during conformational changes

Abstract: The structural elucidation of membrane proteins continues to gather pace, but we know little about their molecular interactions with the lipid environment or how they interact with the surrounding bilayer. Here, with the aid of low-resolution X-ray crystallography, we present direct structural information on membrane interfaces as delineated by lipid phosphate groups surrounding the sarco(endo)plasmic reticulum Ca 2 + -ATPase (sERCA) in its phosphorylated and dephosphorylated Ca 2 + -free forms. The protein-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
110
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 54 publications
7
110
1
Order By: Relevance
“…This result was similar for higher X PC , suggesting that the increase of t(EP) is related to the physical state of the micelles or bicelles and not to changes in the bilayer thickness. In agreement with these findings, Sonntag et al (15) suggested that a change in the bilayers hydrophobic thickness in SERCA may have a direct effect on the conformational change between the E 1 and E 2 states.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This result was similar for higher X PC , suggesting that the increase of t(EP) is related to the physical state of the micelles or bicelles and not to changes in the bilayer thickness. In agreement with these findings, Sonntag et al (15) suggested that a change in the bilayers hydrophobic thickness in SERCA may have a direct effect on the conformational change between the E 1 and E 2 states.…”
Section: Discussionmentioning
confidence: 58%
“…Although the detergent molecules would probably increase the membrane fluidity, it has been demonstrated that the thickness of a bilayer composed of C 12 E 8 and DOPC (in a ratio of 30:80 (i.e. an X PC of about 0.3)) remained nearly constant with respect to a pure phospholipid (15). Importantly, the protein structure was only slightly affected by the detergent environment, consistent with its functional integrity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Two speculative models on ABC-type flippases have been proposed, the "tilting model" and the "rotating helix model", that are however not exclusive [93,216]. In the tilting model, a variation of the alternating access model, the lipid enters the chamber of MsbA from the inner leaflet of the bilayer.…”
Section: Putative Catalytic Mechanism Of Abc Transporters Of the "Expmentioning
confidence: 99%
“…Critical lipid dependencies have also been established for P-type ATPases. The Ca 2þ -transporting P-type ATPase SERCA1a is unstable in the absence of lipids (64), requires an~30-Å -thick lipid bilayer for optimal function (65,66), and induces local deformations in the surrounding lipid bilayer (67). Likewise, the function of copper-transporting P-type ATPases is lipid dependent, since proteins solubilized in detergent are inactive in the absence of supplemented lipids (9,68,69).…”
Section: Discussionmentioning
confidence: 99%